“influencia del ph y dosis de hidróxido de aluminio sobre el porcentaje de eliminación de sulfatos en agua de mina artificial mediante tratamiento por precipitación mineral” - Castillo Lopez, Víctor Manuel (2016)
In the present research, the influence of pH and dose of aluminum hydroxide on the sulphates removal percentage present in artificial mine water, by means of mineral precipitation treatment was evaluated. For the research, the artificial mine water was prepared, utilizing supplies chemical grade (99%) of CuSO4, K2SO4, MgSO4, Na2SO4, FeCl3.6H2O and MnSO4 in amounts of 5.00, 4.00, 3.00, 1.50, 0.30 and 0.20 g of each reactant, dissolved in 5.00 L of distilled water, to obtain a final chemical composition of 1740, 400, 360, 120, 100, 24, 14 and 12 ppm of SO4 2-, Cu2+, K+, Mg2+, Na+, Cl-, Mn2+ and Fe2+ respectively, with a pH 3.60 as initial parameters, that are physicochemical characteristics similar to acid mine drainage (AMD) studied by Geldenhuys (2003) and Cadorin (2007), which served as model for this study. The research has utilized precipitation reactions during successive stages for removing sulfates, beginning with the raising of pH until approximately 10, by adding lime, Ca(OH)2, where the Cu, Mg, Mn and Fe presents in the solution were precipitated as hydroxides, subsequently removed from artificial mine water by filtration. Then was applied the dose of 2.0, 2.5 y 3.0 g/L of aluminum hydroxide, Al(OH)3, previous adjustment of pH to 11.5, 12.0 y 12.5, to ambient temperature and a constant agitation of 1200 rpm, to form a combined salt of calcium, aluminum and sulphate, that remove this ultimate. By using the spectrophotometer T80 + UV-VIS and the standard test method for determining sulphate ions in water, according to ASTM D 516, we proceeded to measure the content of residual sulphate solutions compared this value with the initial values previous treatment, it was possible to evaluate the percentage removal of sulphates. Final results indicated that at pH 11.50 and dose of aluminum hydroxide of 2.0 g/L, it was achieved an 89.62% sulphates removal. Also it is demonstrated with the analysis of variance (ANOVA), that the independent variables significantly affect the percentage removal of these anions